Just Luck: An Experimental Study of Risk-Taking and Fairness - Cappelen, Alexander W; Konow, James; Sørensen, Erik Ø; Tungodden, Bertil (American Economic Review, 2013)
Choices involving risk significantly affect the distribution of income and wealth in society. This paper reports the results of the first experiment, to our knowledge, to study fairness views about risk-taking, specifically whether such views are based chiefly on ex ante opportunities or on ex post outcomes. We find that, even though many participants focus exclusively on ex ante opportunities, most favor some redistribution ex post. Many participants also make a distinction between ex post inequalities that reflect differences in luck and ex post inequalities that reflect differences in choices. These findings apply to both stakeholders and impartial spectators. (JEL D63, D81, H23)